2022
DOI: 10.1097/corr.0000000000002375
|View full text |Cite
|
Sign up to set email alerts
|

Can Technology Assistance be Cost Effective in TKA? A Simulation-Based Analysis of a Risk-prioritized, Practice-specific Framework

Abstract: Background Robotic, navigated, and patient-specific instrumentation (PSI) TKA procedures have been introduced to improve component placement precision and improve implant survivorship and other clinical outcomes. However, the best available evidence has shown that these technologies are ineffective in reducing revision rates in the general TKA patient population. Nonetheless, it seems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…I'm referring to factors such as younger age, higher BMI, and perhaps men. This is what Hickey et al [3] explored in an exciting follow-up study, published in this month's Clinical Orthopaedics and Related Research ® .…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…I'm referring to factors such as younger age, higher BMI, and perhaps men. This is what Hickey et al [3] explored in an exciting follow-up study, published in this month's Clinical Orthopaedics and Related Research ® .…”
mentioning
confidence: 76%
“…It makes less sense to worry about the cost-effectiveness of a modality that has not proven to be effective. Hickey et al [3] help us realize that TA-TKA may not help to reduce the revision rates and might prove cost effective in the usual patients who undergo TKA (older women). The study showed TA-TKA had modest yet promising effectiveness in patients with an elevated risk.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
See 2 more Smart Citations
“…Technology-assistance is also a plausible means of reducing revision risk in a patient population at higher risk of revision. 28 Investigators have reported that pre-surgical planning, computer navigation, and robotic-assistance can potentially lower the risk of rTHA due to dislocation among patients with SPP. Vigdorchik et al found that preoperative planning for rTHA due to recurrent instability resulted in 97% (108/111) survival-free dislocation at two years compared to 84% (93/111) for historical controls whereby 77% of the inappropriately positioned acetabular components would have been unrecognized without biplanar radiographs or stereoradiographic images to identify spinal deformity and spinal stiffness, which suggests an RRR of 75%.…”
Section: Discussionmentioning
confidence: 99%